A field guide to the insects of America north of Mexico - Borror, Donald J. (Donald Joyce), 1907-1988.; White, Richard E. (Boston : Houghton Mifflin, 1970)
Comprehensive, thoroughly illustrated guide to the collection, preservation and study of over five hundred families of North American insects.
Arthropods -- Insects : Proturans -- Bristletails -- Springtails -- Mayflies -- Dragonflies and damselflies -- Grasshoppers, kaytdids, crickets, mantids, walkingsticks, and cockroaches -- Termites -- Stoneflies -- Earwigs -- Webspinners -- Zorapterans -- Booklice and barklice -- Chewing lice -- Sucking lice -- Thrips -- Bugs -- Cicadas, hoppers, whiteflies, aphids, and scale insects -- Fishflies, snakeflies, lacewings, and antlions -- Beetles -- Twisted-winged parasites -- Scorpionflies and their allies -- Caddisflies -- Butterflies and moths -- Flies -- Fleas -- Sawflies, ichneumons, chalcids, ants, wasps, and bees.
Includes bibliographical references (pages 373-376) and index.
Keywords: Insects -- United States -- Identification; Insects -- Canada -- Identification; Insects -- Classification; Guidebooks